Real time interactive learning systems over SSL IPv6 for next generation network - Sameon S.S.; Ismail M.N.; Mohd N. (International Association for Information, Culture, Human and Industry Technology, 2023)
This paper presents the development of next generation e-learning systems for real-time video, voice conferencing and streaming technology over secure socket layer (SSL) IPv6 in campus environment. Development of the V2oIP e-learning systems has contributed a significant value to distance learning. The aim of this study is to design real time interactive learning systems with security over SSL IPv6 for next generation network. This study shows the process and development of e-learning systems with V2oIP technology. Based on the results of this study, it is successfully develop e-learning systems with V2oIP technology over SSL IPv6 for distance learning system. From the result analysis, there is no significant difference between V2oIP SSL IPv6 and V2oIP SSL IPv4 performance issues. It also shows that IPv6 with difference Operating System (OS) has generated low usage RAM and CPU performance. Therefore, implementation of V2oIP e-learning system over SSL IPv6 (next generation network) is able to create mobility and a secure environment for undergraduate and postgraduate students.